Technical-economic relationships of Pampean beekeeping through canonical correlations. (Veterinary Science, 2019)
This study explores the relationship among size and productivity variables with the economic performance of beekeeping. For thi purpose, 40 production units located in La Pampa were analyzed. The results obtained from the canonical analysis indicate a strong positive correlation between the economic performance variables and the size  of the production unit. Therefore, any variation that occurs in the size of the farm should produce a change in the same sense of economic performance. This suggests that most beekeepers produce at increasing returns to scale.
Keywords: honey; scale; productivity; multivariate analysis